La publicidad como origen de la derrota a Google en el derecho al olvido (2014)
This article proposes a critical reflection on the case of theSpanish internet user Mario Costeja in his fight against Googlesearch engine. Mario Costeja exercised his right of oppositionto the handling of his personal data against Google Spain, S. L.,Google Inc. and La Vanguardia Ediciones S.L. The rejection ofboth companies against his petition resulted in a claim before“Agencia Española de Protección de Datos” that ended up in theEuropean Court of Justice. This article describes all the processand collects all voices involved in the trial, with the purpose ofoffering a reflexive construction of a pioneer judgment bindingupon all the member States of the European Union.